Investigating the factors affecting postpartum diabetes screening in the patients with gestational diabetes mellitus: a reference tertiary center experience - Eraslan Şahin, Mefkure; Madendağ, Yusuf (Perinatal Medicine Foundation, 2020)
Objective The pregnant women with gestational diabetes mellitus (GDM) are under the risk of developing type 2 diabetes mellitus and cardiovascular disease after labor. The postpartum diabetes screening has a key role to establish the diagnosis of type 2 diabetes and to start necessary treatment at an earlier period. For that purpose, we aimed to investigate the rates of postpartum diabetes screening and the factors affecting these rates in the pregnant women with GDM diagnosis at Kayseri City Hospital which is a reference center. Methods This study was conducted retrospectively in a tertiary center by investigating pregnant women between 18 and 45 years old whose pregnancy follow-ups were done between June 2018 and January 2020. A total of 2652 pregnant women were screened for GDM by 75-g oral glucose tolerance test (OGTT) during routine clinical follow-up and GDM was found in 425 (16%) of these pregnant women. Of these 425 pregnant women, 225 who continued their postpartum follow-ups and whose contact information was accessed were included in the study. The patients were separated into two groups according to their preference of undergoing postpartum diabetes screening. The demographic characteristics, follow-up numbers and gestational complications of the groups were compared statistically. Results We found that only 34.6% (78/225) of the patients included in the study underwent postpartum diabetes screening and 147 (65.4%) of them did not prefer to undergo postpartum screening. There was no difference between the groups in terms of maternal demographic characteristics. It was found that the patients underwent more postpartum diabetes screening tests in a statistically significant way in cases of the need for antenatal insulin treatment, antenatal visit number being >10 and the presence of antenatal complication (p<0.001, p<0.001, p<0.001, respectively) which are among the gestational characteristics. Conclusion We found that only 34.6% (78/225) of the pregnant women with GDM diagnosis underwent postpartum diabetes screening, and the need for antepartum insulin treatment, antenatal visit number being more than 10 and the presence of antenatal complications were the important factors affecting screening rates. The patients with GDM should be informed again about the importance of undergoing postpartum diabetes particularly near the labor period and during discharge after labor and the Type 2 diabetes risk should be explained in detail after labor.